2019
DOI: 10.1002/chem.201901060
|View full text |Cite
|
Sign up to set email alerts
|

Regiochemistry Control by Bipyridine Substituents in the Deprotonation of ReI and MoIIN‐Alkylimidazole Complexes

Abstract: Compounds containing N‐alkylimidazoles (N‐RIm) and 4,4′‐disubstituted 2,2′‐bipyridines (4,4′‐R′2bipy) coordinated to cationic {Mo(η3‐C4H7)(CO)2} and {Re(CO)3} fragments undergo deprotonation of the C2‐H group of the N‐RIm ligands in their reactions with KN(SiMe3)2. The resulting internal nucleophile adds either to one pyridyl ring, which becomes dearomatized and can undergo ring opening in the subsequent reaction with excess MeOTf, or to the metal center, yielding imidazol‐2‐yl complexes, which in turn add HOT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 96 publications
0
7
0
Order By: Relevance
“…4 Furthermore, coordination to a metal ion also preorganizes the substrates via a geometric control, facilitating their subsequent coupling in regio-and stereoselectivity. 5 In addition, highly activated intermediates such as N and S radicals can be stabilized by coordination to a metal ion via electron delocalization. 6 Indeed, the oxidation of metal−thiolate complexes into metal−thiyl radical intermediates, affording disulfides via S−S radical coupling, is well-documented (see Scheme 1a).…”
Section: ■ Introductionmentioning
confidence: 99%
“…4 Furthermore, coordination to a metal ion also preorganizes the substrates via a geometric control, facilitating their subsequent coupling in regio-and stereoselectivity. 5 In addition, highly activated intermediates such as N and S radicals can be stabilized by coordination to a metal ion via electron delocalization. 6 Indeed, the oxidation of metal−thiolate complexes into metal−thiyl radical intermediates, affording disulfides via S−S radical coupling, is well-documented (see Scheme 1a).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Rhenium complexes containing dearomatized pyridyl rings from intramolecular nucleophilic addition have been protonated or methylated at the amido nitrogen [14a, b] . Examples of protonation at a carbon atom have been found in complexes containing dearomatized 4,4′‐X 2 ‐2,2′‐bipyridine (X=OMe, [14a] NMe 2 ), [14e] for which the preference for carbon (over the amido nitrogen) protonation was attributed to the presence of the resonance electron‐donating groups, which increased the nucleophilicity of the C3 and C5 carbon atoms of the dearomatized pyridyl ring. The tert ‐butyl substituent in the chelates of 4M‐C4 and 4 m‐C4 could be playing a similar role, leading to functionalization of the 3 position upon both protonation and methylation.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, we showed that bipy and phen coordinated to cationic fac ‐rhenium(I) tricarbonyl [14] or cis ‐molybdenum(II) dicarbonyl [14a, e] fragments are not chemically inert ligands [15] and can undergo, under very mild conditions, the addition of internal nucleophiles generated, in most cases, by deprotonation of appropriately positioned co‐ligands (Scheme 1 a). As a result of the additions being intramolecular, the C(sp 3 ) centers were built on the chelate positions closest to the metal fragment—C2 upon deprotonation of SMe 2 [16] and C6 upon deprotonation of N ‐alkylimidazoles, [14a, b, e] PMe 3 , [17] or α‐methyl‐ N ‐heterocycles [18] . Outer‐sphere MeLi addition to coordinated bipy and phen ligands of fac ‐[Re(N‐N)(CO) 3 (PMe 3 )]OTf (N‐N=bipy, phen, Scheme 1 b) complexes [17b] suggests that chelate identity plays a role in the site‐selectivity of the addition.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that 2,2′-bipyridine (bipy) and 1,10-phenanthroline (phen) coordinated to cationic fac -rhenium­(I) tricarbonyl fragments are not chemically inert ligands and can undergo, under mild conditions, the addition of internal nucleophiles generated, in most cases, by deprotonation of appropriately positioned coligands. In the particular case of the deprotonation of 1-methylimidazole (N-MeIm) coordinated to fac -{Re­(bipy)­(CO) 3 }, followed by the action of excess MeOTf, the pyridine ring contraction concomitant with C–N bond scission was obtained ([ A ] in Scheme ). As we have demonstrated more recently, this type of pyridine ring-opening process is favored by more electron-rich cis -rhenium­(I) dicarbonyl complexes, obtained from fac -{Re­(CO) 3 } species by carbonyl substitution by a more σ-donor trimethylphosphane ligand.…”
Section: Introductionmentioning
confidence: 99%